If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.2(z + -2) = 2 + -1x Reorder the terms: 1.2(-2 + z) = 2 + -1x (-2 * 1.2 + z * 1.2) = 2 + -1x (-2.4 + 1.2z) = 2 + -1x Solving -2.4 + 1.2z = 2 + -1x Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2.4' to each side of the equation. -2.4 + 2.4 + 1.2z = 2 + 2.4 + -1x Combine like terms: -2.4 + 2.4 = 0.0 0.0 + 1.2z = 2 + 2.4 + -1x 1.2z = 2 + 2.4 + -1x Combine like terms: 2 + 2.4 = 4.4 1.2z = 4.4 + -1x Divide each side by '1.2'. z = 3.666666667 + -0.8333333333x Simplifying z = 3.666666667 + -0.8333333333x
| 6x(2x-7)=x | | 6y+5=39 | | 4z/(-16)=(-16) | | -17-x=-35 | | 5m+11(12+7m)=5m-8(-6m-2) | | s^2-19s=-88 | | 3m/5-3/20 | | -4y+x+z=6 | | r(b-3)+t(b-3)= | | 18=15+a | | 29=13+b | | 4(b-2)=2(5-6) | | 0.02q+2.1r=3.16-.2r | | -2(x-4)=3x+7 | | 16x^2-10x^2+8x=0 | | 18-m=16 | | 5p-6p=1 | | 5r+4s= | | 10(6x-2)=+4(12x+6) | | s^2-19s+88=0 | | (2x+5)+(5x-7)=18 | | 1/4x=1/4x | | 6=-5a+4a | | 31-4(2x+11)=19 | | 3+3x+3=x-1 | | .74(x-12)=12 | | b-4=-4-4b | | 2m+6+4m=-6 | | ln(2x+1)(x+2)=2ln(x+2) | | 11x-2(3x+7)=6 | | -10d=4 | | 4x-4/5x=64 |